2018
DOI: 10.1109/tsp.2018.2831622
|View full text |Cite
|
Sign up to set email alerts
|

Symbol Error Rate Performance of Box-Relaxation Decoders in Massive MIMO

Abstract: The maximum-likelihood (ML) decoder for symbol detection in large multiple-input multiple-output wireless communication systems is typically computationally prohibitive. In this paper, we study a popular and practical alternative, namely the Box-relaxation optimization (BRO) decoder, which is a natural convex relaxation of the ML. For iid real Gaussian channels with additive Gaussian noise, we obtain exact asymptotic expressions for the symbol error rate (SER) of the BRO. The formulas are particularly simple, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 42 publications
0
99
0
Order By: Relevance
“…where p(x) = 1 √ 2π e −x 2 /2 is the pdf of a standard Gaussain random variable and Q(x) is its associated Q-function. The expectation in (19) can be found in a similar way.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…where p(x) = 1 √ 2π e −x 2 /2 is the pdf of a standard Gaussain random variable and Q(x) is its associated Q-function. The expectation in (19) can be found in a similar way.…”
Section: Resultsmentioning
confidence: 53%
“…The proof of Theorem 2 is also based on the CGMT and largely follows the proof of Theorem 1 but is omitted for space limitations (see [19] for a similarly detailed treatment). Remark 1 (Small/Large Regularizers).…”
Section: Resultsmentioning
confidence: 99%
“…The BRO is a relaxation of (1) to an efficient convex quadratic program, namelyx = sign arg min x∈[−1,1] n y − Ax 2 . Its performance in the large-system limit has been recently analyzed in [10]. Regarding the performance of (1), Tse and Verdu [14] have shown that the BER approaches zero at high-SNR.…”
Section: Settingmentioning
confidence: 99%
“…In particular, the MFB corresponds to the probability of error in detecting (say) x0,1 ∈ {±1} from y = x0,1a1 + z, where y = y − n i=2 x0,iai is assumed known, and ai is the i th column of A (eqv., the MFB is the error probability of an isolated transmission of only the first bit over the channel). It can be shown (e.g., [10]) that the MFB is given by Q( √ δ SNR). Combining this with (a straightforward re-parametrization of) Theorem 3.1 it follows that the BER of (1) satisfies…”
Section: Upper Boundmentioning
confidence: 99%
See 1 more Smart Citation